Playgrounds as microbial interfaces : strategies to enhance soil microbiomes and support healthy childhoods - Manninen, Juulia; Korhonen, Aku; Johnson, Karen L.; Tahvonen, Outi; Luukkonen, Anna; Saarenpää, Mika; Puhakka, Riikka; Uimonen, Laura; Kummola, Laura; Skevaki, Chrysanthi; Renz, Harald; Rajaniemi, Juho; et al. (American Society for Microbiology, 2026)
Emerging evidence suggests that reduced exposure to biodiversity, including rich environmental microbiota, is associated with negative outcomes in the health and well-being of children. Biodiversity loss not only impacts individual health but also poses significant threats to planetary health. It destabilizes systems that regulate climate, purify air and water, maintain soil fertility, and support plant and microbial life essential for environmental health. Here, we review the scientific evidence on microbiome-supportive strategies in eco-centric, child-friendly playground environments. Investigating how environmental features influence soil microbiomes and exposure pathways could provide insights into how playgrounds function as living interfaces. These are places where environmental microbes shape children’s microbial colonization patterns, immune and endocrine regulatory systems, while also contributing to ecosystem services such as biodiversity support and pollutant mitigation—particularly relevant given that many pollutants are known to disrupt immune and endocrine functions in children. These dynamics have far-reaching implications for child well-being, preventive health strategies, physical activity, environmental literacy, and broader sustainability. A multi-omic systems approach offers a critical pathway to uncover the ecological and health-related impacts of nature-associated microbial exposure and characterize host–microbiome interactions underlying immune and endocrine regulation, brain development, cognition, and stress-related disorders. Our review highlights a lack of such integrative studies, underscoring the need to advance this line of research to inform evidence-based, sustainable, and health-promoting urban design.
Keywords: children (age groups); health; microbiome; planetary health; human microbiome; hostresponse; environmental microbiology; biodiversity; immune regulation; ecosystemservices; multi-omics